2016
DOI: 10.1586/14737167.2016.1154790
|View full text |Cite
|
Sign up to set email alerts
|

Over-the-counter medicine and dietary supplement consumption among academic youth in Poland

Abstract: This version is available at https://strathprints.strath.ac.uk/55549/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 11 publications
3
14
0
Order By: Relevance
“…The vast majority (91%) of our respondents had secondary or higher education and only 9% had an elementary or vocational education. This data was similar to the Barrenberg and Garbe outcomes in the German population, also to the Calamusa outcomes in Italy, and to the Bochenek outcomes in Poland (18)(19)(20). Different results were obtained in Sweden by Hakonsen where no differences in the educational level were observed (16).…”
Section: Disscusion and Conclussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The vast majority (91%) of our respondents had secondary or higher education and only 9% had an elementary or vocational education. This data was similar to the Barrenberg and Garbe outcomes in the German population, also to the Calamusa outcomes in Italy, and to the Bochenek outcomes in Poland (18)(19)(20). Different results were obtained in Sweden by Hakonsen where no differences in the educational level were observed (16).…”
Section: Disscusion and Conclussionsupporting
confidence: 85%
“…Half of the respondents read the information on the leaflet (51%). Also in the Bochenek and Wozniak-Holecka studies, a majority of patients interviewed found information about products on the leaflet (20,21). Most respondents, as reported by Calamusa, read the leaflet every time they bought an herbal medication (18).…”
Section: Disscusion and Conclussionmentioning
confidence: 99%
“…Nonetheless, such an attitude of Polish pharmacists may result from the common access of OTC medicines in Poland. Apart from pharmacies, some OTC medicines might be available from herbal shops, groceries and petrol stations (2,19). In light of the inevitable growth of the OTC drug market and an increase in the number of RX-to-OTC switches, it could be advisable to create classes of OTC drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmaceuticals belong to the most heavily advertised goods in terms of advertising budgets, thus the overwhelming scope of information coming from media may contribute to miscomprehension. It is confirmed by the observation that more than 30% of Poles make their OTC drug choices based on advertising (19). Therefore, medicines can be misused or overused by the patients who, wrongly convinced that they know everything about medicines or fail to read OTC drugsí leaflets (2).…”
Section: Rx Otcmentioning
confidence: 98%
“…In Poland the over-the-counter (OTC) medications and dietary supplements became popular in the last decades [1]. Almost 90% of households in Poland acquire medical drugs without prescription of a physician -in the most cases this way are bought painkillers and non-steroid-anti-inflammatory drugs [2].…”
Section: Introductionmentioning
confidence: 99%